2019
DOI: 10.1101/510057
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensitivity analysis of agent-based simulation utilizing massively parallel computation and interactive data visualization

Abstract: An essential step in the analysis of agent-based simulation is sensitivity analysis, which namely examines the dependency of parameter values on simulation results. Although a number of approaches have been proposed for sensitivity analysis, they still have limitations in exhaustivity and interpretability. In this study, we propose a novel methodology for sensitivity analysis of agent-based simulation, MASSIVE (Massively parallel Agent-based Simulations and Subsequent Interactive Visualization-based Exploratio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…In both the driver and driver-d models, we do not consider spatial information. However, it should be noted that, by simulating tumor growth on a one-dimensional lattice, we demonstrated that the spatial bias of a resource necessary for cell divisions could prompt the driver-branching process (Niida et al, 2019).…”
Section: /21mentioning
confidence: 81%
See 4 more Smart Citations
“…In both the driver and driver-d models, we do not consider spatial information. However, it should be noted that, by simulating tumor growth on a one-dimensional lattice, we demonstrated that the spatial bias of a resource necessary for cell divisions could prompt the driver-branching process (Niida et al, 2019).…”
Section: /21mentioning
confidence: 81%
“…Recently reported studies have shown that spatial structures regulate evolutionary dynamics in tumors (Noble et al, 2019;West et al, 2019). We also determined that resource bias prompts the driver-branching process, by simulating tumor growth on a one-dimensional lattice (Niida et al, 2019). Moreover, Iwasaki and Innan 2017 -Giner et al, 2015).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations